2007
DOI: 10.1111/j.1540-8159.2007.00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pacing in Congenital Complete Atrioventricular Block of Immunological Origin: Interest of Multisite Stimulation

Abstract: An infant with a congenital auriculoventricular block (CAVB) of immunological origin was diagnosed prenatally. The mother had Gougerot-Sjögren disease with positive anti-Sjogren's Syndrome A (SSA) and Sjogren's Syndrome B (SSB) serologies. Cardiac pacing was necessary and the epicardial route was chosen. Considering the left ventricular (LV) dilatation, bi-ventricular (BiV) stimulation was preferred to the usual DDD mode, presumed to have a deleterious long-term effect. Echographic parameters were better with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Chronic right ventricular pacing in patients with complete atrioventricular block is associated with left ventricular dyssynchrony causing deleterious left ventricular remodelling and decreased exercise capacity. 6 In order to prevent dyssynchrony of the left ventricle induced by pacing, Rumeau et al 7 reported primary implantation of a biventricular pacemaker in children with complete atrioventricular block. 7 Our method of biventricular pacing could minimise the adverse effects of conventional right ventricular pacing, such as QRS prolongation and inducible left ventricular dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic right ventricular pacing in patients with complete atrioventricular block is associated with left ventricular dyssynchrony causing deleterious left ventricular remodelling and decreased exercise capacity. 6 In order to prevent dyssynchrony of the left ventricle induced by pacing, Rumeau et al 7 reported primary implantation of a biventricular pacemaker in children with complete atrioventricular block. 7 Our method of biventricular pacing could minimise the adverse effects of conventional right ventricular pacing, such as QRS prolongation and inducible left ventricular dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
“…6 In order to prevent dyssynchrony of the left ventricle induced by pacing, Rumeau et al 7 reported primary implantation of a biventricular pacemaker in children with complete atrioventricular block. 7 Our method of biventricular pacing could minimise the adverse effects of conventional right ventricular pacing, such as QRS prolongation and inducible left ventricular dyssynchrony. Biventricular pacing by conventional methods, however, requires greater pacemaker battery usage and a larger epicardial space for implantation, which is considered unsuitable for young children; moreover, primary biventricular pacemaker implantation is not allowed in Japan for a diagnosis of complete atrioventricular block.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the potential relationship between left ventricular dysfunction in patients with complete atrioventricular block (CAVB) and conventional apical right ventricular pacing, we would like to add some findings which were not discussed by Rumeau et al 1 …”
mentioning
confidence: 99%